Kemunculan Media Baru dan Pengaruhnya Terhadap Masyarakat Digital : Suatu Tinjauan Kritis Berdasarkan Pemikiran Jean Baudrillard - Wilio Joseph Donatius Kalesaran (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2023)
Throughout the ages, humans have always created technology that helps their lives. In the field of human communication, new media is present as a consequence of the rapid development of technology. Today, its most obvious manifestation is the internet. According to Jean Baudrillard, postmodern society is a consumer society that continuously consumes objects in the form of signs. In the context of new media, they consume information. Objects are manipulated as signs actively. The process then equates the true reality with signs. This is what Baudrillard calls a simulation. Simulation disguises reality in the form of the meaning of signs. It represents models that approach the facts. Thanks to the presence of the media, we cannot differentiate between simulation and reality. This condition is called Baudrillard as hyperreality or 'beyond reality'. Today, new media simulates itself. It presents the public with a new reality called the virtual world. Communities interact with each other virtually. In this virtual reality, information is continuously being produced as a commodity. As for information, it cannot be destroyed and continues to accumulate. This accumulation of information causes a void or 'implosion'. Fake signs (pseudo sign) glides freely as information and transforms into a beautiful spectacle. Ultimately society can lose its critical power and be led to catastrophe.